- 3x - 6 = 4(2 - 3x) - 8x
- Solving multi-step equations can look hard, but once you break it down into steps, its easy!
- 3x - 6 = 4(2 - 3x) - 8x3x -6 = 8 - 12x -8x
- First, use the distributive property on the values in the parenthesis.
- 3x - 6 = 4(2 - 3x) - 8x
- 3x -6 = 8 - 12x -8x3x - 6 = 8 - 20x
- Next, you add or subtract the like terms on either side of the equals sign. In this case, that means the values with x.
- Then add or subtract the like terms.
- 3x - 6 = 4(2 - 3x) - 8x
- 3x - 6 = 8 - 20x -3x -3x -6 = 8 - 23x
- Then you subtract the smaller x value on both sides.
- Then add or subtract the like terms.
- -6 = 8 - 23x -8 -8 14 = -23x
- 3x - 6 = 4(2 - 3x) - 8x
- After that, you subtract the 8 on both sides. You want to get the 23x by itself.
- Then add or subtract the like terms.
- 14 = -23x -23x -23x 14/23 = x 1.64 = x
- 3x - 6 = 4(2 - 3x) - 8x
- Then add or subtract the like terms.
- Finally, you divide both sides by -23x. This gets you 14/23 or 1.64 equals x.